2020
DOI: 10.1017/s0025315420000922
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive seasonality and the gonadal maturation of silver pomfret Pampus argenteus in the Bay of Bengal, Bangladesh

Abstract: The silver pomfret (Pampus argenteus) is one of the most commercially important marine fish species in the Bay of Bengal, Indian Ocean. However, detailed information on the reproductive biology of silver pomfret is limited for the Bay of Bengal, Bangladesh. To understand their reproductive biology, especially the gonadal developmental cycle and spawning season, a total of 373 individuals were collected monthly from February 2016 to January 2018 and examined. The total length (TL) and weight (TW) of P. argenteu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
1
6
1
Order By: Relevance
“…But the previous study recorded the maximum value of TL as 54 cm from the Bay of Bengal that was much higher than our recorded value (Karim et al 2020). Another study found the value of TL as 30.9 cm from the Bay of Bengal (Cox's Bazar) which was lower than our finding (Akhter et al 2020). This maximum length (38 cm) was also smaller than the fish of 56.2 cm caught from the Persian Gulf (Sahraei et al 2018) and 45 cm from the Indonesian coast (Damora et al 2018).…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…But the previous study recorded the maximum value of TL as 54 cm from the Bay of Bengal that was much higher than our recorded value (Karim et al 2020). Another study found the value of TL as 30.9 cm from the Bay of Bengal (Cox's Bazar) which was lower than our finding (Akhter et al 2020). This maximum length (38 cm) was also smaller than the fish of 56.2 cm caught from the Persian Gulf (Sahraei et al 2018) and 45 cm from the Indonesian coast (Damora et al 2018).…”
Section: Discussioncontrasting
confidence: 62%
“…This study showed the isometric growth pattern of P. niger where the b value was close to 3 (b = 2.981), which indicates that the length increases proportionally with the body weight and this trend of proportional growth continues throughout the life. Both Akhter et al (2020) and Karim et al (2020) found negative allometric growth for this pomfret fish in the Bay of Bengal, where the values of b were less than 3. The fish also showed negative allometric growth (b < 3) in the Kuwait coast of the Arabian Gulf (Dadzie et al 2008).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Pampus argenteus and Euthynnus affinis) was higher during the winter, which might be due to their breeding season. The availability of rupchanda Pampus argenteus, for instance, was observed throughout the year, with two breeding periods during April and October (Akhter et al, 2020). Although the availability of medium-sized hilsa Tenualosa ilisha was observed during the winter, the standard size of hilsa was usually observed during the monsoon season (September-October) because of their breeding season (Rahman et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the males mature earlier than females, and two peaks of gonad maturation were observed in Kuwait, one in March-May and the other during August-September, in both males and females (Almatar et al, 2004;Lone et al, 2008a). In the East China Sea and India, the spawning peaks were from May to July and October (Akhter et al, 2020). Although the morphology of the testicular development process during the spawning period and mature sperm has been described in pomfret (Lone et al, 2008b;Zhao et al, 2010), there are no detailed descriptions of the testicular parameters, particularly the ultrastructure related to spermatogenesis in cultured pomfret.…”
mentioning
confidence: 99%